2017
DOI: 10.1111/febs.14307
|View full text |Cite
|
Sign up to set email alerts
|

The Radical SAM enzyme NirJ catalyzes the removal of two propionate side chains during heme d1 biosynthesis

Abstract: Heme d is a modified tetrapyrrole playing an important role in denitrification by acting as the catalytically essential cofactor in the cytochrome cd nitrite reductase of many denitrifying bacteria. In the course of heme d biosynthesis, the two propionate side chains on pyrrole rings A and B of the intermediate 12,18-didecarboxysiroheme are removed from the tetrapyrrole macrocycle. In the final heme d molecule, the propionate groups are replaced by two keto functions. Although it was speculated that the Radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Alternatively, a role of NirF as a biosynthetic enzyme could be envisaged, potentially involved in the introduction of the carbonyl functions at C3 and C8 of rings A and B. While it has been shown that the cytoplasmic Radical SAM enzyme NirJ removes the two propionate moieties at C3 and C8 of 12,18-didecarboxysiroheme (DDSH) [17] and that the periplasmic NirN converts the propionate at C17 to an acrylate group in the final step of the pathway [18,17], the formation of the carbonyl functions at C3 and C8 is still enigmatic. Although it was speculated that NirJ might also be responsible for the oxidation of these position, the installation of the carbonyls by NirJ has not been observed experimentally so far [17,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, a role of NirF as a biosynthetic enzyme could be envisaged, potentially involved in the introduction of the carbonyl functions at C3 and C8 of rings A and B. While it has been shown that the cytoplasmic Radical SAM enzyme NirJ removes the two propionate moieties at C3 and C8 of 12,18-didecarboxysiroheme (DDSH) [17] and that the periplasmic NirN converts the propionate at C17 to an acrylate group in the final step of the pathway [18,17], the formation of the carbonyl functions at C3 and C8 is still enigmatic. Although it was speculated that NirJ might also be responsible for the oxidation of these position, the installation of the carbonyls by NirJ has not been observed experimentally so far [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…The first steps of heme d1 biosynthesis are the conversion of uroporphyrinogen III to 12,18didecarboxysiroheme (DDSH) via percorrin-2, sirohydrochlorin and siroheme, successively catalyzed by NirE, CysG (in some organisms) and NirDLGH (Figure 1) [13][14][15][16]. The intermediate DDSH is further converted by the Radical SAM enzyme NirJ, which sequentially removes the propionate groups from pyrrole rings A and B [17]. Based on mass spectrometry, a tetrapyrrole with two γ-lactones involving the acetate groups at C2 and C7 has been observed as the final product of this reaction, but these lactones may be artifacts of the extraction procedure and alternatives such as hydroxyl groups or hydrogen replacing the propionate chains were proposed [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of how glutamate is formed, tetrapyrrole biosynthesis proceeds by combining eight glutamate molecules into the 40‐carbon uroporphyrinogen III. Two additional methyl carbons are added to uroporphyrinogen III from methionine, via a S ‐adenosyl methionine (SAM) reaction to form precorrin‐2 (Boss, Oehme, Billig, Birkemeyer, & Layer, ; Singh et al, ; Storbeck et al, , ; Zajicek et al, ). These methyl groups likely come from methyl‐H 4 MPT which delivers the methyl group to homocysteine to form methionine.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative pathway in class II methanogens produces 2-oxoglutarate with this ratio at 2:3. Birkemeyer, & Layer, 2017;Singh et al, 2016;Storbeck et al, 2011Storbeck et al, , 2009Zajicek et al, 2009). These methyl groups likely come from methyl-H 4 MPT which delivers the methyl group to homocysteine to form methionine.…”
Section: Carbon Assimilation Pathwaymentioning
confidence: 99%